Transgenic plants for the production of veterinary vaccines - Dus Santos, María José (2005)
The expression of antigens in transgenic plants has been increasingly used in the development of experimental vaccines, particularly oriented to the development of edible vaccines. Hence, this technology becomes highly suitable to express immunogenic proteins from pathogens. Foot and mouth disease virus, bovine rotavirus and bovine viral diarrhoea virus are considered to be the most important causative agents of economic loss of cattle production in Argentina, and they are thus optimal candidates for alternative means of immunization. Here, we present a review of our results corresponding to the expression of immunogenic proteins from these three viruses in alfalfa transgenic plants, and we discuss the possibility of using them for the development of plant-based vaccines.